An ultrathin and broadband radar absorber using metamaterials. Issue 5 (3rd September 2021) - Zhou, Bi Cheng; Wang, Dong Hong; Ma, Jiang Jiang; Li, Bao Yi; Zhao, Ya Juan; Li, Ke Xun
Abstract : In this article, the design, simulation, fabrication and measurement of an ultrathin and wide band radar metamaterial absorber (MMA) are introduced. The unit of the MMA consists of two different sizes of L-shaped structure and a perfect electric conductor separated by 2 mm dielectric layer (only 0.074 λ to 0.156 λ at lowest and highest frequencies, respectively). The simulation results show that the proposed MMA has more than 90% good absorption (below −10 dB) in the frequency range of 11.07–23.36 GHz. By adjusting the scale of the unit, the absorption characteristics of the proposed absorber can be adjusted and moved to the frequency range which we are interested in. The absorption mechanism of the proposed absorber is also analyzed by field and surface current distributions. The proposed absorber has been fabricated and experimentally tested for absorbing properties at different angles of incidence and different polarizations. The experimental results show the absorption rates are consistent with the simulation results. The proposed absorber has potential applications in stealth technology.